2013
DOI: 10.1519/jsc.0b013e3182510886
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Explosive Power Production Using the Backward Overhead Shot Throw and the Effects of Morning Resistance Exercise on Afternoon Performance

Abstract: The purpose of this study was to determine if performing a morning total-body resistance exercise workout affects explosive power in an afternoon session. The secondary goal was to assess the usefulness of the backward overhead shot throw (BOST) as a measure of explosive power in experienced thrower in the sport of athletics. Throwers (N = 14) performed 1 control and 1 experimental trial on separate days. The control consisted of BOST and a vertical jump (VJ) testing performed in the afternoon. For the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 25 publications
1
65
1
Order By: Relevance
“…A study by Cook et al (2014) found that when a 3 RM back squat protocol was performed in the morning, strength was improved when tested in the afternoon. Similarly, Ekstrand et al (2013) showed that resistance exercise in the morning improved explosive power 4–6 h later. However, afternoon and evening strength training can be positively influenced by the body’s natural circadian rhythm and optimal core temperature (Teo et al, 2011a,b) and thus may contribute at least in part to these findings.…”
Section: Discussionmentioning
confidence: 85%
“…A study by Cook et al (2014) found that when a 3 RM back squat protocol was performed in the morning, strength was improved when tested in the afternoon. Similarly, Ekstrand et al (2013) showed that resistance exercise in the morning improved explosive power 4–6 h later. However, afternoon and evening strength training can be positively influenced by the body’s natural circadian rhythm and optimal core temperature (Teo et al, 2011a,b) and thus may contribute at least in part to these findings.…”
Section: Discussionmentioning
confidence: 85%
“…The next day, all athletes performed two different shot put tests: (a) the backward overhead shot put throw and (b) the shot put throw from the power position (Zaras et al, 2016). The backward overhead shot put throw is considered to be a whole-body power test with minimal technically demands (Ekstrand et al, 2013). However, the shot put throw from the power position is considered to be a highly technically demand throwing test.…”
Section: Shot Put Testsmentioning
confidence: 99%
“…Shot put throwing tests such as the underhand hot put throw and the backward overhead shot put throw (Ekstrand et al, 2013) are used to evaluate whole-body power performance; and explosive exercises are employed for throwing performance improvement by several track and field throwers (Terzis et al, 2010;Zaras et al, 2014). Performance in backward overhead shot put throw was found to be positively correlated with the hammer throwing performance [r = 0.95, (Terzis et al, 2010)].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study by Ingham et al 22 reported substantial improvements in 800-m time-trial performance when preceded by 200-m repetitions 3 hours before the time trial. Further research has demonstrated that morning resistance exercise can positively affect afternoon performances in elite-level athletes.…”
Section: Morning Exercisementioning
confidence: 99%